Some extended Tauberian theorems for (A)(k) (C, Î±) summability method - Çanak, Ä°brahim (Acta Scientiarum. Technology, 2014)
In this paper, some new Tauberian conditions are introduced for (A)(k) (C, Î±) summability method. Â